Caracterización de los sedimentos para mejorar el criterio de diseño de los sedimentadores en el ámbito del Proyecto Especial Chavimochic - Sánchez Tisnado, Paulo César (2009)
Thís research aíms to characterize the sedíments and suspended solíds leavíng the desanding to optimize the design of the sediments in the Special Project CHAVIMOCHIC Suspended solids without causing a number of drawbacks in the pressurized irrigation system, resulting in a reduction in the lifetime of the equipment and other elements of the system, resulting in negative effects on the cost of operation and production systems and crops. The settlers are a simple and economical solution for the removal of suspended /solids (sand, silt and el ay). May be designed to be the characteristics of the sediments such as size, shape, weight, speed and mineralogical composition offall. Sediment characterization was performed in the first and second phase of the Special Project CHA VIMOCHIC at the following stations: S. Desanding, S. The Agony, S. Cargo House, S. 10 E. Side Rinconada. As the most important stations along the system. The most important characteristics of the sedíments is that they are very fine particles with the greatest diameter 0.25 - 0.3mm up particles even smaller than 0.0015mm. These particles are formed by a majority of silt and clay with only 4% of fine sand. lts specific weight on average 2.64 g/cc and specífic weíght of submerged 1.05 g/cc. In íts mineral composítion domínated by quartz with a 70.5%. As for the sedimentatíon rate ís a function ofparticle diameter to settle for a diameter of0.05mm is the speed of0.25cm/s, as for a partícle ofO.Olmm has a speed ofO.Ollcm/s.